Principales parásitos intestinales en aves de la orden galliforme género faisán,revisión bibliográfica (2021)
In this bibliographic review, the main intestinal parasites in birds of the galliform order are determined. 33 documents were reviewed including scientific articles, graduate work and research, of which 15% were developed in Colombia. It was determined that the most prevalent parasite in gastrointestinal infections in birds of the galliform order is Eimeria spp with 79% of findings in laboratory tests performed. In the same way, the possible conventional and unconventional treatments were reviewed, finding that 86% of the documents did not state that they had found an effective treatment to eradicate Eimeria from the body; however, it was also found that 3% recommended the use of Levamisole, Febendazole and Piperazine as conventional medical treatment and the use of garlic and ginger in 7% as alternative medical treatment. Finally, it was determined that the probable causes of the acquisition of the parasite were the asepsis of the beds and sheds where the birds in question are, in addition to overcrowding and poor nutrition.